Interferon‐gamma gene polymorphism +874 A/T is associated with an increased risk of cytomegalovirus infection among Hispanic renal transplant recipients. Issue 5 (11th September 2014) - Vu, D.; Shah, T.; Ansari, J.; Sakharkar, P.; Yasir, Q.; Naraghi, R.; Hutchinson, I.; Min, D.
Abstract Background Cytomegalovirus (CMV) is the most common cause of viral infection, causing morbidity and mortality among renal transplant recipients (RTRs). Cytokines such as tumor necrosis factor‐alpha (TNF‐α), interleukin‐10 (IL‐10), and interferon‐gamma (IFN‐γ) have been shown to possess antiviral properties, and their polymorphisms are associated with disease outcome. The aim was to investigate the association of gene polymorphisms in IL‐10, IFN‐γ, and TNF‐α with CMV infection in RTRs. Methods IL‐10 −1082 A>G, −592 A>C; TNF‐α −308 A>G; and IFN‐γ +874 A>T gene polymorphisms were studied in 247 Hispanic RTRs (52 RTRs with CMV infection and 195 without CMV infection), using DNA‐based polymerase chain reaction with sequence‐specific primers and restriction. Results Median time to CMV infection was 8 months, with a mean peak CMV viral load of 25, 314 copies/mL. Patients with donor‐positive/recipient‐negative (D+/R−) serostatus were found to be associated with a high risk of CMV infection (P = 0.001). A statistically significant correlation was found between IFN‐γ +874 A>T polymorphism and the risk of CMV infection. The IFN‐γ +874 AA genotype was associated with a 3.4‐fold increased risk for the CMV‐infected group compared to the non‐CMV group (odds ratio = 3.4, 95% confidence interval = 1.24–9.34, P = 0.01). The association was independently significant in multiple logistic regression (P = 0.01), along with serologic status D+/R−, acute rejection, and anti‐thymocyte globulin induction. The allelic as well as genotypic frequencies of TNF‐α and IL‐10 did not significantly differ between the CMV‐infection group and the control group. Individuals with IFN‐γ +874 AT and AA genotypes exhibited higher risk of allograft loss. Conclusion This study suggested that RTRs with variant homozygous IFN‐γ AA genotype were at risk of CMV infection, whereas the high producer IFN‐γ +874 TT genotype appears to be associated with lower risk of CMV infection.